1 т = 10 ц:
1 т - 4 ц = 1 * 10 - 4 = 10 - 4 = 6 ц
4 т 8 ц - 5 ц = 4 т + (8 ц - 5 ц) = 4 т 3 ц
52 т 6 ц - 20 т = (52 т - 20 т) + 6 ц = 32 т 6 ц
1 т = 1 000 кг:
1 т - 250 кг = 1 * 1 000 - 250 = 750 кг
8 т 600 кг - 3 т = (8 т - 3 т) + 600 кг = 5 т 600 кг
10 т - 10 ц = 10 * 10 - 10 = 100 - 10 = 90 ц
1 т = 10 ц:
1 т - 4 ц = 1 * 10 - 4 = 10 - 4 = 6 ц
4 т 8 ц - 5 ц = 4 т + (8 ц - 5 ц) = 4 т 3 ц
52 т 6 ц - 20 т = (52 т - 20 т) + 6 ц = 32 т 6 ц
1 т = 1 000 кг:
1 т - 250 кг = 1 * 1 000 - 250 = 750 кг
8 т 600 кг - 3 т = (8 т - 3 т) + 600 кг = 5 т 600 кг
10 т - 10 ц = 10 * 10 - 10 = 100 - 10 = 90 ц